Electron Beam Pasteurization and Complementary Food Processing Technologies. - Pillai, Suresh (Woodhead Publishing in food science, technology, and nutrition ;, 2014)
Food safety is a constant challenge for the food industry. Electron Beam Pasteurization and Complementary Food Processing Technologies explores applications in conjunction with other food processing technologies.